2001
DOI: 10.1177/0022487101052002002
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teachers for Culturally Diverse Schools

Abstract: This article reviews data-based research studies on preservice teacher preparation for multicultural schools, particularly schools that serve historically underserved communities. In this article, the author reviews 80 studies of effects of various preservice teacher education strategies, including recruiting and selecting students, cross-cultural immersion experiences, multicultural education coursework, and program restructuring. Although there is a large quantity of research, very little of it actually exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
279
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,265 publications
(293 citation statements)
references
References 69 publications
6
279
0
8
Order By: Relevance
“…Therefore, congruent with current multicultural and teacher education research (Gunn et al 2013;Sleeter 2008), we suggest a need for continued emphasis on and collective responsibility for supporting teachers across the developmental spectrum in critically reflecting on their own cultural beliefs and values when learning about teaching culturally and linguistically diverse children. Odom et al (2012) reported that the training and support available to early childhood providers is often inadequate or unavailable and called for improved professional development that helps providers understand developmentally and culturally appropriate practices.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, congruent with current multicultural and teacher education research (Gunn et al 2013;Sleeter 2008), we suggest a need for continued emphasis on and collective responsibility for supporting teachers across the developmental spectrum in critically reflecting on their own cultural beliefs and values when learning about teaching culturally and linguistically diverse children. Odom et al (2012) reported that the training and support available to early childhood providers is often inadequate or unavailable and called for improved professional development that helps providers understand developmentally and culturally appropriate practices.…”
Section: Discussionsupporting
confidence: 62%
“…For these teachers, instead of being an opportunity for professional growth, children's cultural tools and identities were perceived as a barrier to delivering instruction, making assessments, and developing as a teacher. Therefore, unlike the current rhetoric in multicultural education concerning how a majority of White preservice and inservice teachers adopt a color-blind stance in the classroom (Sleeter 2008;Ullucci and Battey 2011), teachers at Kids Play were very much conscious of color and culture. However, for some teachers, this consciousness coupled with learning to teach became too much of a complex cognitive and socially constructive process.…”
Section: Desensitization Of Classroom Culturementioning
confidence: 90%
“…This resonates with international research that school populations in western nations are becoming more diverse while teachers continue to be White and female (Feistritzer, 2011;Landsman & Lewis, 2006;Sleeter, 2008).…”
mentioning
confidence: 58%
“…On this account, the teacher is viewed neither as the sole nor even the primary fount of knowledge (Ladson-Billings, 1995;McCutcheon, 2002). Above all, the aim of CRP is to sustain (Paris, 2012) and validate students' background culture by drawing from their native "funds of knowledge" (Moll, Amani, Neff, & Gonzalez, 1992;Sleeter, 2001), which includes language, histories and cultural practices (Gay, 2001). Funds of knowledge practices promote a dialogue-centered (de Mello, 2012) classroom where conversation-broadly conceived-is viewed as the chief mode of educational experience (Applebee, 1996).…”
Section: Funds Of Knowledgementioning
confidence: 99%